2021
DOI: 10.1044/2020_jslhr-20-00287
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Measures for Studying Language Comprehension Deficits in Aphasia: A Systematic Search and Scoping Review

Abstract: Aim The aim of this scoping review is to identify the eye tracking paradigms and eye movement measures used to investigate auditory and reading comprehension deficits in persons with aphasia (PWA). Method MEDLINE via PubMed, Cochrane, CINAHL, Embase, PsycINFO, OTseeker, Scopus, Google Scholar, Grey Literature Database, and ProQuest Search (Dissertations & Theses) were searched for relevant studies. The Covidence software was used to manage the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…By comparing noun-verb homonym pairs with related meanings (e.g., to crash/the crash ) to noun-verb homonym pairs with unrelated meanings (e.g., to squash/the squash ), they found different noun/verb selection patterns but no effect of meaning relatedness. Lastly, studies using eye-tracking to investigate the processing of lexical ambiguity in individuals with aphasia suggested that they have intact lexical access processes, but have specific impairments in lexical integration and/or reanalysis processes ( Laurinavichyute et al, 2014 ; see Sharma et al, 2021 for a review). Specifically, individuals with non-fluent agrammatic aphasia have performed at chance when processing sentences that involved reanalysis (e.g., object relatives “ This is the man that the boy catches” and sentences with lexical ambiguity “ The PEN is always packed with wooly sheep” ) ( Friedmann and Gvion, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing noun-verb homonym pairs with related meanings (e.g., to crash/the crash ) to noun-verb homonym pairs with unrelated meanings (e.g., to squash/the squash ), they found different noun/verb selection patterns but no effect of meaning relatedness. Lastly, studies using eye-tracking to investigate the processing of lexical ambiguity in individuals with aphasia suggested that they have intact lexical access processes, but have specific impairments in lexical integration and/or reanalysis processes ( Laurinavichyute et al, 2014 ; see Sharma et al, 2021 for a review). Specifically, individuals with non-fluent agrammatic aphasia have performed at chance when processing sentences that involved reanalysis (e.g., object relatives “ This is the man that the boy catches” and sentences with lexical ambiguity “ The PEN is always packed with wooly sheep” ) ( Friedmann and Gvion, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…A last direction for future work in terms of methodological advances is the use of eye tracking for the investigation of morphosyntactic processing in AD. This technique has been implemented in the last fifteen years for the study of sentence comprehension in people with stroke‐induced aphasia and primary progressive aphasia, and it has proven to be a valuable method to uncover similarities and differences in sentence processing between patients and non‐brain damaged controls (see Sharma et al., 2021, for a scoping review). Research that has implemented eye tracking for the study of AD has focused on the investigation of cognitive decline in AD and on using it in the classification, diagnosis or early prediction of AD (see Readman et al., 2021, for a systematic review).…”
Section: Discussionmentioning
confidence: 99%
“…The left eye was recorded. The experimental stimuli were presented on a Display PC via Experiment Builder®, an object-oriented programming suite specifically designed to administer stimuli while recording eye movements (for details on eye-tracking procedures and measures, see Duchowski, 2017 ; Rayner, 1998 ; and Sharma et al, 2021 ). Sentence presentation was preceded by a fixation point and triggered manually by the experimenter.…”
Section: Methodsmentioning
confidence: 99%